Identifying Chinese college EFL students’ needs for an oral communication instruction module / Wang Yang and Soo Ruey Shing - Wang, Yang; Soo, Ruey Shing (Universiti Teknologi MARA, 2024)
This study examines the difficulties encountered by Chinese college students who are learning English as a foreign language (EFL) in oral communication. It also offers recommendation for the creation of a specialised module called the Oral Communication Instruction Module (OCIM) to address their specific needs. The research employs a mixed-methods technique to collect quantitative data from 394 third-semester students and qualitative insights through semi-structured interviews from 20 students and 8 experienced EFL instructors from a public university in China. The findings indicate significant challenges in grammatical accuracy, pronunciation, speech fluency, and the use of effective communication strategies. These obstacles hinder students’ competence to effectively participate in academic and social situations, impacting their overall language skills and self-assurance. The study highlights the importance of integrating practical communication tasks, engaging teaching approaches, and a supportive classroom environment to tackle these problems. The proposed OCIM seeks to address deficiencies in oral communication competence, such as pronunciation challenges, limited vocabulary, and ineffective communication strategies, by offering a well-organized and thorough framework tailored to the specific needs of Chinese students learning English as a foreign language, which include targeted pronunciation practice, vocabulary development, and culturally relevant communication strategies. The curriculum aims to promote students’ academic achievement, increase their employability in a globalised job market, and boost their confidence in using English by enhancing their oral communication abilities. This research provides significant insights for educators and policymakers who are seeking to enhance EFL instruction and increase student learning outcomes.